2021
DOI: 10.14309/ctg.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer in Alaska Native and American Indian People Living in Alaska, 1990–2017

Abstract: INTRODUCTION: Alaska Native (AN) people experience a high burden of gastric cancer compared with other US Native and non-Native populations. Previous reports have suggested that gastric cancer in AN people occurs at a younger age and is a more aggressive pathologic type. We evaluated all cases of gastric cancer in AN people from 1990 to 2017 and compared the epidemiologic and pathologic characteristics with the gastric cancers that occurred in the same time in the US white (USW) population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In contrast, H. pylori infection is the principal risk factor for noncardia tumors 131 . H. pylori is most common in persons with lower SES and is especially prevalent in Alaska Native individuals 132,133 …”
Section: Selected Findingsmentioning
confidence: 99%
“…In contrast, H. pylori infection is the principal risk factor for noncardia tumors 131 . H. pylori is most common in persons with lower SES and is especially prevalent in Alaska Native individuals 132,133 …”
Section: Selected Findingsmentioning
confidence: 99%
“…Exact prognosis based on non-cardia versus cardia is inconclusive, but a recent study (2021) indicated that cardia variants may lead to worse outcomes [43]. A cause of concern among Alaska Native individuals is the high rate of antimicrobial resistance, which may affect the treatment efficacy of therapies targeted against H. pylori [7,44]. Reinfection has also been found to occur among Alaska Natives after treatment [7,44].…”
Section: H Pylorimentioning
confidence: 99%
“…A cause of concern among Alaska Native individuals is the high rate of antimicrobial resistance, which may affect the treatment efficacy of therapies targeted against H. pylori [7,44]. Reinfection has also been found to occur among Alaska Natives after treatment [7,44]. Smoking has also been found to decrease antibiotic treatment efficacy of H. pylori among the Indigenous population of Taiwan [4].…”
Section: H Pylorimentioning
confidence: 99%
See 2 more Smart Citations